Developing the public health workforce through community-based fieldwork. Issue 1 (2nd January 2022) - Schober, Daniel J.; Carlberg-Racich, Suzanne; Dirkes, Jessica
Abstract: A skilled public health workforce is critical to assure the public's health. Recent scholarship has highlighted the benefits of practice-based fieldwork to train the public health workforce. This scholarship has highlighted these benefits primarily through quantitative evaluation. DePaul University's Master of Public Health (MPH) Program provides practice-based education and training to enable students to develop key competencies in public and community health. A key component of the MPH Program is a 9-month practicum experience. This practicum experience requires students to (1) Complete at least 250 h of fieldwork at a local health organization and (2) write a capstone thesis about their practicum project. In this themed issue, seven MPH Program students provide empirical papers, describing their practicum project and the competencies they gained. These empirical papers build upon existing scholarship on practice-based fieldwork and aim to advance academic and community efforts to assure a skilled public and community health workforce.